The Effects of Independent Director Litigation Risk* - Donelson, Dain C.; Tori, Elizabeth; Yust, Christopher G. (Contemporary Accounting Research, 2022)
ABSTRACT Does personal litigation risk for independent directors materially affect firm valuation, compensation‐related issues for independent directors, and board composition decisions? We use the unexpected In re Investors Bancorp decision in 2017 by the Delaware Supreme Court, which lowered the liability threshold only for directors in derivative litigation over their own equity grants and increased their future litigation risk, to examine these issues. Understanding changes in independent director litigation risk is important because such changes may affect directors' willingness or ability to serve on boards and advise executives. Consistent with our predictions, investors and firms reacted to the decision. First, Delaware firms experienced significant negative short‐window returns, concentrated in high‐litigation‐risk firms where equity compensation is most important. Second, Delaware firms responded by increasing the use of director compensation caps, highlighting that they did not pay excessive amounts. Third, Delaware firms with higher abnormal director compensation decreased director compensation, while those with lower abnormal director compensation did not. Finally, Delaware firms added higher‐quality directors to the compensation committee, consistent with concerns about heightened litigation risk for those positions. Notably, these new, higher‐quality directors did not accept lower pay, unlike holdover directors who previously served on the committee. Overall, results are consistent with director litigation concerns having a significant effect on shareholder value and firm and director behavior.